2020
DOI: 10.4143/crt.2020.337
|View full text |Cite
|
Sign up to set email alerts
|

Challenge for Diagnostic Assessment of Deep Learning Algorithm for Metastases Classification in Sentinel Lymph Nodes on Frozen Tissue Section Digital Slides in Women with Breast Cancer

Abstract: Assessing the status of metastasis in sentinel lymph nodes (SLNs) by pathologists is an essential task for the accurate staging of breast cancer. However, histopathological evaluation of SLNs by a pathologist is not easy and is a tedious and time-consuming task. The purpose of this study is to review a challenge competition (HeLP 2018) to develop automated solutions for the classification of metastases in hematoxylin and eosin-stained frozen tissue sections of SLNs in breast cancer patients. Materials and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The clinical-grade pathology using was trained by weakly supervised deep learning with over thousands of slides dataset including prostate core biopsy, breast cancer metastatic lymph node, and skin lesion separately; and the area under the curve (AUC) can be 0.965 on the test of breast axillary lymph node metastasis [8]. The accuracy of the weakly supervised deep learning may be affected by the labels [9] and the size of the dataset which could be improved by upgrading the algorithm iteration [11][12][13]. Atsushi Teramoto improves 4% AUC by using a two-step supervised strategy for the classification of lung cytological images with 60 cases dataset [14].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical-grade pathology using was trained by weakly supervised deep learning with over thousands of slides dataset including prostate core biopsy, breast cancer metastatic lymph node, and skin lesion separately; and the area under the curve (AUC) can be 0.965 on the test of breast axillary lymph node metastasis [8]. The accuracy of the weakly supervised deep learning may be affected by the labels [9] and the size of the dataset which could be improved by upgrading the algorithm iteration [11][12][13]. Atsushi Teramoto improves 4% AUC by using a two-step supervised strategy for the classification of lung cytological images with 60 cases dataset [14].…”
Section: Introductionmentioning
confidence: 99%
“…In a challenge using the same FFS lymph node biopsy specimens, teams prediction times and accuracies varied significantly despite using the same data. The strongest performing team (AUC 0.805) took 10.8 min per slide to process while the next highest (AUC 0.776) took only 0.6 min 20 …”
Section: Resultsmentioning
confidence: 99%
“…The strongest performing team (AUC 0.805) took 10.8 min per slide to process while the next highest (AUC 0.776) took only 0.6 min. 20 Models have also been shown to have strong performance in differentiating types of cancer from one another, even when trained on FFPE images and tested on FFS images. 21 This can be aided by adding rules which predispose a model to be more conservative, calling uncertain tissue malignant in an attempt to reduce false negatives.…”
Section: Diagnosis and Classification Of Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Histological artefacts present in frozen sections can hinder rapid diagnostic assessments during surgery 14 , but a deep-learning algorithm may improve the quality of whole-slide images (WSIs) from H&E-stained frozen sections, leading to more accurate tumor classi cation by pathologists 15 . Recent studies have also shown the ability of deep learning models to diagnose thyroid nodules 16 and determine the metastatic status of sentinel lymph nodes in breast cancer 17 from the conventional intraoperative frozen sections, highlighting the potential of frozen samples in developing deep learning models. Thus, we hypothesize a deep learning approach can facilitate the intraoperative diagnosis of brain tumors.…”
Section: Introductionmentioning
confidence: 99%